2021
DOI: 10.1155/2021/6619527
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Mesenchymal Stem Cell-Centered Therapies in Temporomandibular Joint Osteoarthritis

Abstract: Temporomandibular joint osteoarthritis (TMJOA) is a degenerative disease characterized by cartilage degeneration, disrupted subchondral bone remodeling, and synovitis, seriously affecting the quality of life of patients with chronic pain and functional disabilities. Current treatments for TMJOA are mainly symptomatic therapies without reliable long-term efficacy, due to the limited self-renewal capability of the condyle and the poorly elucidated pathogenesis of TMJOA. Recently, there has been increased interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 190 publications
0
12
0
1
Order By: Relevance
“…Possible unfavorable directions for stem cell differentiation, including proinflammatory phenotype-producing pro-inflammatory cytokines, are being cautioned about [ 83 , 84 , 85 , 86 ]. The issue requires further investigation but does not appear to be a deterrent to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Possible unfavorable directions for stem cell differentiation, including proinflammatory phenotype-producing pro-inflammatory cytokines, are being cautioned about [ 83 , 84 , 85 , 86 ]. The issue requires further investigation but does not appear to be a deterrent to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Dang et al recently demonstrated that an advanced therapeutic application combining adipose tissue-derived mesenchymal stem cells and dermal-derived collagen could promote cartilage regeneration [ 39 ]. Recent studies reported that repetitive injections of exogenous BMSCs could relieve cartilage degeneration in temporomandibular joint osteoarthritis (TMJ-OA) in rodent models [ 16 , 40 ]. However, the effective migration of donor cells toward the target tissue and chondrogenic differentiation still hinder the application of MSCs-based therapy on the TMJ region [ 18 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that repetitive injections of exogenous BMSCs could relieve cartilage degeneration in temporomandibular joint osteoarthritis (TMJ-OA) in rodent models [ 16 , 40 ]. However, the effective migration of donor cells toward the target tissue and chondrogenic differentiation still hinder the application of MSCs-based therapy on the TMJ region [ 18 , 40 ]. Lu et al reported that multiple-time injections of GFP-BMSCs into the TMJ region rescued cartilage degeneration in mice TMJ-OA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…达 [35] ;降低了实验性自身免疫性关节炎的进展和 炎症因子的滑膜表达,提示 NST-1s 可能可以通过 抑制程序性坏死介质的表达,降低炎症因子的分 泌,从而延缓关节炎的进展 [36] 。 颞下颌关节骨关节炎是最难治疗的骨关节 炎之一,而近年来该病的发病率逐渐升高,是口腔 临床研究的热点。颞下颌关节骨关节炎的主要病 理学特征包括软骨细胞死亡、细胞外基质降解和 软骨下骨重塑,但确切发病机制和过程仍有待进 一步研究 [37][38] 。Zhang 等 [35] 实验证明,下颌软骨…”
Section: 证明,髁突软骨退变时程序性坏死的关键分子unclassified